The Effect of Digital Transformation on Supply Chain Management and Industrial Firm Performance of Small and Medium-Sized in the United Arab Emirates - Noura Khamis Sowaif; Hashem Osamah Yahya Mohammed (Asian Scholars Network, 2026)
Indexed by MyCite